Physics for engineering applications - Puri, Sanjiv (Alpha Science International, 2010)
Introduces the fundamental concepts pertaining to important sub-fields of physics, namely, Waves, Optics, Electromagnetics, Quantum Mechanics, Radiation Physics and Solid-State Physics. This book is suitable for B E / B Tech students taking up Applied Physics course, as well as those appearing for GATE exams and A M I E students.